7(t-2)-t=

Simple and best practice solution for 7(t-2)-t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(t-2)-t= equation:


Simplifying
7(t + -2) + -1t = 0

Reorder the terms:
7(-2 + t) + -1t = 0
(-2 * 7 + t * 7) + -1t = 0
(-14 + 7t) + -1t = 0

Combine like terms: 7t + -1t = 6t
-14 + 6t = 0

Solving
-14 + 6t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 6t = 0 + 14

Combine like terms: -14 + 14 = 0
0 + 6t = 0 + 14
6t = 0 + 14

Combine like terms: 0 + 14 = 14
6t = 14

Divide each side by '6'.
t = 2.333333333

Simplifying
t = 2.333333333

See similar equations:

| 0=9a^2-4a | | 22x^2-11x-8= | | x^2+2x-4=-2x+1 | | 22x^2-10x-8= | | 22x^2-31x-8= | | -8x-11(x+5)=-2(9x+2) | | x^2+7=1 | | 40x^2+12x-28= | | 40x^2+5x-28= | | 7y+3(y-4)=3(y+1)-2 | | 4x+6=-24 | | -4(t-3)+8t=9t-2 | | -3x+5=-5x-8 | | 2x+7=36 | | 3(x+4)=7x+5-4x+7 | | 3x+12y=12 | | 35+.15m=117.15 | | 49-n^2=0 | | 55-2x=20 | | -5x-21=3x+11 | | x=5-6+-4 | | x^2+10x+38=0 | | 4x+1=-5x+1 | | x=3-6 | | x=3-5 | | M^3-25m=0 | | 0.11k+1.5=2.40 | | 5x^2+13x-3=7x-4 | | 3x^2-5r-1=0 | | 13-7(a+2)=7+a | | -2x-7=-3x+10 | | 5x+2+5=-3x |

Equations solver categories